A nitrogen-doped Mo x C / Co / carbon nanotube composite material and preparation method and application thereof
By coating the surface of the separator of lithium sulfur batteries with nitrogen-doped MoxC/Co/carbon nanotube composites, the problems of low conductivity and insufficient catalytic capacity of the existing separator are solved, and the energy density and cycle life of the lithium sulfur batteries are significantly improved.
Patent Information
- Application Number
- CN202111646895.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-12-30
AI Technical Summary
The separators of existing lithium-sulfur batteries have problems such as low conductivity, weak conversion capacity between catalytic polysulfides, and insufficient adsorption capacity of polysulfides, which makes it difficult to improve the electrochemical performance.
The nitrogen-doped MoxC/Co/carbon nanotube composite material is used as the partition layer. By coating the composite material on the surface of the traditional membrane, the "shuttle effect" of polysulfide is suppressed and the electrochemical performance is improved.
It effectively improves the energy density and cycle life of lithium-sulfur batteries, significantly suppresses the "shuttle effect", and improves the electrochemical performance.
Smart Images

Figure CN114300668B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a nitrogen-doped Mo x C / Co / carbon nanotube composite material and its preparation method and application. Background Art
[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the growth of the world's population and economic development, today's society has an increasing demand for energy, while the excessive consumption and exploitation of fossil fuels have caused the continuous deterioration of the ecological environment. Countries around the world are constantly increasing the development and utilization of renewable energy such as solar energy and wind energy. However, due to the intermittent and unstable nature of renewable energy, the development of efficient and economical energy storage and conversion systems has become more urgent. Lithium-ion batteries with graphite as negative electrode materials have been widely used in various fields of people's lives, especially in portable electronic devices, due to their high energy density and long cycle life. However, the rapid development of electronic devices and electric vehicles has further increased society's energy demand and put forward higher requirements for energy storage systems. Lithium-ion batteries are about to reach the limit of their energy density. Therefore, lithium-sulfur batteries with higher theoretical energy density are increasingly attracting attention and have become one of the most promising next-generation electrochemical energy storage systems.
[0004] Different from the insertion / extraction mechanism of lithium-ion batteries, the principle of lithium-sulfur batteries is the redox reaction between the sulfur element at the positive electrode and the lithium metal at the negative electrode. Its theoretical specific capacity is as high as 1675 mAh g -1 , mass specific energy density is 2500Wh kg -1 , volumetric energy density is 2800Wh L -1 In addition, sulfur, the cathode active material of lithium-sulfur batteries, is abundant in the earth's crust, cheap, and environmentally friendly. Therefore, lithium-sulfur batteries are more environmentally friendly while providing higher energy density.
[0005] However, the actual lithium-sulfur battery is far from its theoretical performance, such as low energy density and poor cycle life. In order to solve the above problems, researchers have made a lot of efforts in the positive electrode, negative electrode, electrolyte and other aspects in recent years, focusing on solving the conductivity of the positive electrode material, reducing the "shuttle effect" in the reaction process, and protecting the metal lithium negative electrode. In all the studies, the modified separator is a simple and easy way to directly solve the shuttle effect of lithium-sulfur batteries. The modified separator is placed between the positive electrode and the diaphragm to hinder the diffusion of polysulfide ions to the negative electrode and inhibit the "shuttle effect"; at the same time, the separator can adsorb polysulfide ions in the electrolyte and act as a secondary current collector to reduce the loss of active substances and improve the electrochemical performance of lithium-sulfur batteries. However, the inventors found that the current separator has problems such as low conductivity, catalytic conversion between polysulfides, and weak adsorption capacity for polysulfides, which makes it difficult to improve the electrochemical performance of lithium-sulfur batteries. Summary of the invention
[0006] In view of the above problems, the present invention provides a nitrogen-doped Mo x C / Co / carbon nanotube composite material and its preparation method and application. The present invention effectively suppresses the "shuttle effect" of polysulfide in lithium-sulfur battery after coating the composite material on the surface of traditional diaphragm, and improves the energy density and cycle life of lithium-sulfur battery. To achieve the above purpose, the present invention discloses the following technical solution.
[0007] In a first aspect of the present invention, a nitrogen-doped Mo is disclosed. x C / Co / carbon nanotube composite material comprising nitrogen-doped two-dimensional sheet-like Mo x C matrix and nitrogen-doped carbon nanotubes in situ grown on the surface of the matrix. x Metal cobalt particles are in-situ grown on the C substrate, and the nitrogen-doped Mo x The nitrogen in the C matrix forms a bond with the matrix in the form of N-Mo; and the nitrogen element in the nitrogen-doped carbon nanotube forms a bond in the form of NC.
[0008] Furthermore, the Mo x The C matrix is MoC or a composite of MoC and Mo2C.
[0009] Furthermore, the nitrogen-doped carbon nanotubes are in a bent and entangled state, and part of the nitrogen-doped carbon nanotubes are from Mo x The C matrix surface extends outward.
[0010] In a second aspect of the present invention, a nitrogen-doped Mo is disclosed. x The preparation method of C / Co / carbon nanotube composite material comprises the following steps:
[0011] (1) The aqueous dispersion of Mo2C MXene and a cobalt source is stirred to form a non-uniform liquid, and then the non-uniform liquid is rapidly frozen and freeze-dried to obtain a Co-Mo2C MXene precursor for later use.
[0012] (2) reducing the introduced cobalt ions to metallic cobalt during the pyrolysis of the carbon source and the nitrogen source to catalyze the heated and gasified carbon source and the nitrogen source to form nitrogen-doped carbon nanotubes on the surface of the Co-Mo2C MXene precursor, thereby obtaining the nitrogen-doped Mo x C / Co / carbon nanotube composites.
[0013] Furthermore, in step (1), the Mo2C MXene is a few-layer Mo2C MXene, that is, the number of layers is controlled to be less than 2 to 3 layers. x The C / Co / carbon nanotube composite material uses a new two-dimensional material, Mo2C MXene, and the two-dimensional layer matrix is strictly controlled to be less than 2 to 3 layers to obtain more active catalytic sites, which can more effectively adsorb polysulfides and catalyze the conversion between polysulfides.
[0014] Optionally, the preparation method of the few-layer Mo2C MXene comprises the steps of: dissolving multi-layer Mo2C MXene in a tetrabutylammonium hydroxide aqueous solution, using tetrabutylammonium hydroxide for intercalation to obtain the few-layer Mo2C MXene, centrifuging after the reaction is completed, washing the solid product with clean water, and then centrifuging to remove the clear liquid to obtain an aqueous dispersion containing the few-layer Mo2C MXene.
[0015] Furthermore, in step (1), the cobalt source includes at least one of cobalt acetate, cobalt nitrate, cobalt chloride, etc. In the present invention, the role of the cobalt element includes: catalyzing the growth of carbon nanotubes and improving the conductivity of the composite material.
[0016] Furthermore, in step (1), the mass ratio of the Mo2C MXene to the cobalt source is in the range of 1:1 to 4. The introduction of nitrogen can effectively improve the adsorption of polysulfides and catalyze the rapid conversion between polysulfides.
[0017] Furthermore, in step (1), the aqueous dispersion of the Mo2C MXene and the cobalt source is stirred for 12 to 18 hours to obtain the heterogeneous liquid.
[0018] Furthermore, in step (1), the non-uniform liquid is rapidly frozen with liquid nitrogen and then freeze-dried in vacuum to obtain a powdered Co-Mo2C MXene precursor. Compared with direct freeze-drying, the vacuum freeze-drying can accelerate the acquisition of the Co-Mo2C MXene precursor and maintain the morphological characteristics of the flaky Mo2C MXene.
[0019] Furthermore, in step (2), the carbon source and the nitrogen source include at least one of dicyandiamide, melamine, urea, etc. The carbon source and the nitrogen source are used to in-situ grow nitrogen-doped carbon nanotubes on Mo2C MXene to obtain nitrogen-doped Mo x C / Co / carbon nanotube composites.
[0020] Furthermore, in step (2), the mass ratio of the carbon source, the nitrogen source and the Co-Mo2C MXene precursor is 1:0.03-0.125.
[0021] Furthermore, in step (2), the carbon source and the nitrogen source are heated and gasified at 800-1000° C. in a protective atmosphere, and kept warm for 1-3 h under this condition, and the cobalt ions are reduced to cobalt particles to catalyze the growth of nitrogen-doped carbon nanotubes on the surface of the Co-Mo2C MXene precursor.
[0022] In a third aspect of the present invention, the nitrogen-doped Mo is disclosed. x Application of C / Co / carbon nanotube composite materials in batteries; preferably, preparing separators for lithium-sulfur batteries. By coating the composite materials on the surface of traditional separators, the "shuttle effect" of polysulfides in lithium-sulfur batteries is effectively suppressed, thereby improving the energy density and cycle life of lithium-sulfur batteries.
[0023] Furthermore, the method for preparing the separator of the lithium-sulfur battery comprises the following steps:
[0024] (i) The nitrogen-doped Mo x The C / Co / carbon nanotube composite material, the conductive agent and the binder are mixed uniformly, and then a solvent is added and mixed uniformly to obtain a slurry.
[0025] (ii) The slurry is uniformly coated on the diaphragm, and then vacuum dried to obtain a Mo-doped diaphragm loaded with nitrogen. x Modified interlayer of C / Co / carbon nanotube composites.
[0026] Furthermore, in step (i), the mass ratio of the composite material, the conductive agent and the binder is 8:1:1.
[0027] Optionally, the conductive agent includes any one of carbon black, conductive graphite, carbon nanotubes, graphene, Ketjen black, acetylene black, Super P, etc.
[0028] Optionally, the binder includes any one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber latex (SBR), carboxymethyl cellulose (CMC), and the like.
[0029] Optionally, the solvent includes any one of 1-methyl-2-pyrrolidone solution, water, and the like.
[0030] Furthermore, in step (ii), the separator comprises any one of a polyolefin microporous membrane such as polyethylene or polypropylene, Celgard 2400, and the like.
[0031] Furthermore, in step (ii), the drying temperature is 50-60°C and the drying time is 6-24 hours. In this step, the solvent in the slurry is removed by vacuum drying, thereby forming a nitrogen-doped Mo film on the surface of the diaphragm. x Modified layer of C / Co / CNT composites.
[0032] Compared with the prior art, the present invention has the following beneficial and unique effects:
[0033] (1) Nitrogen-doped Mo of the present invention x The C / Co / carbon nanotube composite material has the morphology and structure of both one-dimensional carbon nanotubes and two-dimensional MXene. It not only retains the numerous catalytic active sites of two-dimensional MXene, which is beneficial to the catalytic conversion of polysulfides, but also the introduction of carbon nanotubes improves the conductivity of the material and the electrochemical performance of lithium-sulfur batteries.
[0034] (2) Nitrogen-doped Mo of the present invention x The C / Co / carbon nanotube composite material has a large specific surface area due to its morphology and structure of one-dimensional carbon nanotubes and two-dimensional MXene. It can provide more polysulfide adsorption sites, inhibit the diffusion of polysulfides, thereby inhibiting the "shuttle effect" of lithium-sulfur batteries, and significantly improving the energy density and cycle life of lithium-sulfur batteries.
[0035] (3) Nitrogen-doped Mo of the present invention x The introduction of nitrogen into the C / Co / carbon nanotube composite material provides more active adsorption sites for polysulfides, inhibits the diffusion of polysulfides, suppresses the "shuttle effect" of lithium-sulfur batteries, and improves the energy density and cycle life of lithium-sulfur batteries.
[0036] (4) Nitrogen-doped Mo of the present invention x The C / Co / carbon nanotube composite material uses vacuum freeze-drying technology during the preparation process, which can maintain the two-dimensional MXene morphology and structure and reduce the curling or other degrees of damage to the MXene during evaporation or grinding. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein:
[0038] Figure 1 The nitrogen-doped Mo prepared in the first embodimentx X-ray diffraction (XRD) pattern of C / Co / carbon nanotube composites.
[0039] Figure 2 The nitrogen-doped Mo prepared in the first embodiment x Scanning electron microscope (SEM) image of C / Co / carbon nanotube composite material.
[0040] Figure 3 The first cycle capacity diagram of the diaphragms prepared in the first embodiment, the fifth embodiment, the sixth embodiment, and the seventh embodiment at 0.1C. Specific embodiments
[0041] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0042] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If not otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in the present invention are for demonstration purposes only. The present invention is further described according to the accompanying drawings and specific embodiments of the specification.
[0043] First embodiment
[0044] 1. A nitrogen-doped Mo x The preparation method of C / Co / carbon nanotube composite material comprises the steps of:
[0045] (1) Preparation of multilayer Mo2C MXene: 20 ml of deionized water was placed in a polytetrafluoroethylene liner. Under magnetic stirring, 20 ml of 12 mol / L concentrated hydrochloric acid was slowly added. After stirring for 10 min, 3 g of lithium fluoride was added. After thorough mixing, 1 g of Mo2Ga2C MAX was added. After stirring for 30 min, the polytetrafluoroethylene liner was moved to a reactor and then kept at a constant temperature of 180 °C for 36 hours. After the reaction was completed, the solid product was separated by centrifugation, washed with deionized water until the pH was 6, and then the solid product was vacuum dried at 60 °C for 12 h to obtain dark green powdery multilayer Mo2C MXene for later use.
[0046] (2) Preparation of few-layer Mo2C MXene: 0.5 g of the multilayer Mo2C MXene prepared in step (1) was added to 20 ml of a 25% mass concentration of tetrabutylammonium hydroxide aqueous solution and stirred continuously at 35 °C for 12 h. After the reaction was completed, the mixture was transferred to a 50 ml centrifuge tube for centrifugation (8000 rpm). The separated solid product was washed with deionized water. The solid product was then added to a centrifuge tube and 40 ml of deionized water was added and centrifuged at 3500 rpm for 2 min. After removing the upper clear liquid, the lower liquid phase containing the solid product was collected to obtain a dispersion containing few-layer Mo2C MXene for later use.
[0047] (3) Preparation of Co-Mo2C MXene precursor: 0.1 g of cobalt acetate tetrahydrate was dissolved in a dispersion containing 50 mg of the few-layer Mo2C MXene prepared in step (2). After continuous stirring for 12 hours, the mixture was poured into a centrifuge tube and rapidly frozen with liquid nitrogen for 5 minutes. The mixture was then placed in a vacuum freeze dryer and freeze-dried at 6 Pa and -83 °C for 48 hours to obtain a powdered Co-Mo2C MXene precursor for later use.
[0048] (4) Nitrogen-Cobalt Co-doped Mo x Preparation of C carbon nanotube composite material: weigh 1g of dicyandiamide as a nitrogen source and a carbon source and put it into an ordinary porcelain boat, grind the powdered Co-Mo2C MXene precursor of step (3) with a mortar for 5min, weigh 0.1g and put it into a corundum porcelain boat, put the ordinary porcelain boat and the corundum porcelain boat into a tubular furnace at the same time, and place the corundum porcelain boat at the heating center of the tubular furnace, and place the ordinary porcelain boat upstream of the corundum porcelain boat (i.e., on the side of the air inlet of the tubular furnace), then heat to 800℃ at a rate of 5℃ / min in an argon atmosphere and keep it for 2h, then cool to room temperature to obtain nitrogen-doped Mo x C / Co / carbon nanotube composites.
[0049] 2. Preparation of modified interlayer:
[0050] (i) The nitrogen-doped Mo prepared in this embodiment x The C / Co / carbon nanotube composite material, acetylene black and binder polyvinylidene fluoride (PVDF) were ground in a mortar at a mass ratio of 8:1:1, and then 1-methyl-2-pyrrolidone solution was added until the powder was a black viscous slurry for later use.
[0051] (ii) The slurry was uniformly coated on a polypropylene microporous membrane (PP (Celgard-2400) membrane) using a 100 μm scraper, and then the membrane was dried at 60° C. for 6 h, and finally punched into a circular membrane with a diameter of 19 mm to obtain a modified membrane.
[0052] Second embodiment
[0053] 1. A nitrogen-doped Mo x The preparation method of C / Co / carbon nanotube composite material comprises the steps of:
[0054] (1) Preparation of multilayer Mo2C MXene: same as the first embodiment.
[0055] (2) Preparation of few-layer Mo2C MXene: same as the first embodiment.
[0056] (3) Preparation of Co-Mo2C MXene precursor: 50 mg of cobalt nitrate hexahydrate was dissolved in a dispersion containing 50 mg of the few-layer Mo2C MXene prepared in step (2). After continuous stirring for 12 hours, the mixture was poured into a centrifuge tube and rapidly frozen with liquid nitrogen for 5 minutes. The mixture was then placed in a vacuum freeze dryer and freeze-dried at 6 Pa and -83 °C for 48 hours to obtain a powdered Co-Mo2C MXene precursor for later use.
[0057] (4) Nitrogen-doped Mo x Preparation of C / Co / carbon nanotube composite material: weigh 1g of dicyandiamide as a nitrogen source and a carbon source and put it into an ordinary porcelain boat, grind the powdered Co-Mo2C MXene precursor of step (3) with a mortar for 5 minutes, weigh 0.05g and put it into a corundum porcelain boat, put the ordinary porcelain boat and the corundum porcelain boat into a tube furnace at the same time, and place the corundum porcelain boat at the heating center of the tube furnace, and place the ordinary porcelain boat upstream of the corundum porcelain boat (i.e., on the side of the air inlet of the tube furnace), then heat to 800°C at a rate of 5°C / min in an argon atmosphere and keep it for 1h, then cool to room temperature to obtain nitrogen-doped Mo x C / Co / carbon nanotube composites.
[0058] 2. Preparation of modified interlayer:
[0059] (i) The nitrogen-doped Mo prepared in this embodiment x The C / Co / carbon nanotube composite material, Ketjen black and binder polyvinylidene fluoride (PVDF) were ground in a mortar at a mass ratio of 8:1:1, and then 1-methyl-2-pyrrolidone solution was added until the powder was a black viscous slurry for later use.
[0060] (ii) The slurry was uniformly coated on a polypropylene microporous membrane (PP (Celgard-2400) membrane), and then the membrane was dried at 55° C. for 18 h, and finally punched into a circular membrane with a diameter of 19 mm, thereby obtaining a modified membrane.
[0061] Third embodiment
[0062] 1. A nitrogen-doped Mo xThe preparation method of C / Co / carbon nanotube composite material comprises the steps of:
[0063] (1) Preparation of multilayer Mo2C MXene: same as the first embodiment.
[0064] (2) Preparation of few-layer Mo2C MXene: same as the first embodiment.
[0065] (3) Preparation of Co-Mo2C MXene precursor: 0.15 g of cobalt chloride hexahydrate was dissolved in a dispersion containing 50 mg of the few-layer Mo2C MXene prepared in step (2). After continuous stirring for 12 hours, the mixture was poured into a centrifuge tube and rapidly frozen with liquid nitrogen for 5 minutes. The mixture was then placed in a vacuum freeze dryer and freeze-dried at 6 Pa and -83 °C for 48 hours to obtain a powdered Co-Mo2C MXene precursor for later use.
[0066] (4) Nitrogen-doped Mo x Preparation of C / Co / carbon nanotube composite material: weigh 1g of dicyandiamide as a nitrogen source and a carbon source and put it into an ordinary porcelain boat, grind the powdered Co-Mo2C MXene precursor of step (3) with a mortar for 5min, weigh 0.03g and put it into a corundum porcelain boat, put the ordinary porcelain boat and the corundum porcelain boat into a tubular furnace at the same time, and place the corundum porcelain boat at the heating center of the tubular furnace, and place the ordinary porcelain boat upstream of the corundum porcelain boat (i.e., on the side of the air inlet of the tubular furnace), then heat to 800℃ at a rate of 5℃ / min in an argon atmosphere and keep it for 1h, then cool to room temperature to obtain nitrogen-doped Mo x C / Co / carbon nanotube composites.
[0067] 2. Preparation of modified interlayer:
[0068] (i) The nitrogen-doped Mo prepared in this embodiment x The C / Co / carbon nanotube composite material, Super P and binder polyvinylidene fluoride (PVDF) were ground in a mortar at a mass ratio of 8:1:1, and then 1-methyl-2-pyrrolidone solution was added until the powder was a black viscous slurry for later use.
[0069] (ii) The slurry was uniformly coated on a polypropylene microporous membrane (PP (Celgard-2400) membrane), and then the membrane was dried at 60° C. for 6 h, and finally punched into a circular membrane with a diameter of 19 mm to obtain a modified membrane.
[0070] Fourth embodiment
[0071] 1. A nitrogen-doped Mo x The preparation method of C / Co / carbon nanotube composite material comprises the steps of:
[0072] (1) Preparation of multilayer Mo2C MXene: same as the first embodiment.
[0073] (2) Preparation of few-layer Mo2C MXene: same as the first embodiment.
[0074] (3) Preparation of Co-Mo2C MXene precursor: 0.2 g of cobalt acetate tetrahydrate was dissolved in a dispersion containing 50 mg of the few-layer Mo2C MXene prepared in step (2). After continuous stirring for 12 hours, the mixture was poured into a centrifuge tube and rapidly frozen with liquid nitrogen for 5 minutes. The mixture was then placed in a vacuum freeze dryer and freeze-dried at 6 Pa and -83 °C for 48 hours to obtain a powdered Co-Mo2C MXene precursor for later use.
[0075] (4) Nitrogen-doped Mo x Preparation of C / Co / carbon nanotube composite material: weigh 1g of dicyandiamide as a nitrogen source and carbon source and put it into an ordinary porcelain boat, grind the powdered Co-Mo2C MXene precursor of step (3) with a mortar for 5 minutes, weigh 0.125g and put it into a corundum porcelain boat, put the ordinary porcelain boat and the corundum porcelain boat into a tubular furnace at the same time, and place the corundum porcelain boat at the heating center of the tubular furnace, and place the ordinary porcelain boat upstream of the corundum porcelain boat (i.e., on the side of the air inlet of the tubular furnace), then heat to 1000℃ at a rate of 5℃ / min in an argon atmosphere and keep it for 3h, then cool to room temperature to obtain nitrogen-doped Mo x C / Co / carbon nanotube composites.
[0076] 2. Preparation of modified interlayer: same as the first embodiment.
[0077] Fifth embodiment
[0078] Preparation of modified interlayer: Same as the first embodiment, except that the membrane does not contain nitrogen-doped Mo x C / Co / carbon nanotube composite material to verify the nitrogen-doped Mo prepared in the embodiment of the present invention x Effect of C / Co / carbon nanotube composites on the performance of lithium-sulfur batteries.
[0079] Sixth embodiment
[0080] Preparation of modified interlayer:
[0081] (i) The few-layer Mo2C MXene prepared in the first embodiment, acetylene black and binder polyvinylidene fluoride (PVDF) were ground in a mortar at a mass ratio of 8:1:1, and then 1-methyl-2-pyrrolidone solution was added until the powder was a black viscous slurry for later use.
[0082] (ii) The slurry was uniformly coated on a polypropylene microporous membrane (PP (Celgard-2400) membrane) using a 100 μm hanging knife, and then the membrane was dried at 60° C. for 6 h, and finally punched into a circular membrane with a diameter of 19 mm to obtain a modified membrane.
[0083] Seventh embodiment
[0084] 1. A nitrogen-doped Mo x The preparation method of the C composite material comprises the steps of:
[0085] (1) Preparation of multilayer Mo2C MXene: same as the first embodiment.
[0086] (2) Preparation of few-layer Mo2C MXene: same as the first embodiment.
[0087] (3) Nitrogen-doped Mo x Preparation of C composite material: weigh 1g of dicyandiamide as a nitrogen source and a carbon source and put it into an ordinary porcelain boat, vacuum freeze-dry the Mo2C MXene dispersion of step (2), then weigh 0.1g and put it into an ordinary porcelain boat and a corundum porcelain boat, put the corundum porcelain boat into the heating center of a tube furnace, put the ordinary porcelain boat into the upstream of the corundum porcelain boat (i.e., the air inlet side of the tube furnace), then heat it to 800℃ at a rate of 5℃ / min in an argon atmosphere and keep it for 2h, then cool it to room temperature to obtain nitrogen-doped Mo2C MXene. x C composite material.
[0088] 2. Preparation of modified interlayer:
[0089] (i) The nitrogen-doped Mo prepared in this embodiment x The C composite material, acetylene black and binder polyvinylidene fluoride (PVDF) were ground in a mortar at a mass ratio of 8:1:1, and then 1-methyl-2-pyrrolidone solution was added until the powder was a black viscous slurry for later use.
[0090] (ii) The slurry was uniformly coated on a polypropylene microporous membrane (PP (Celgard-2400) membrane) using a 100 μm hanging knife, and then the membrane was dried at 60° C. for 6 h, and finally punched into a circular membrane with a diameter of 19 mm to obtain a modified membrane.
[0091] Performance Testing
[0092] Figure 1 The nitrogen-doped Mo prepared in the first embodiment x The XRD pattern of C / Co / carbon nanotube composite material shows that nitrogen-doped Mo was successfully prepared in this embodiment. x C / Co / carbon nanotube composites.
[0093] Figure 2 The nitrogen-doped Mo prepared in the first embodiment x The SEM image of the C / Co / carbon nanotube composite material shows that the nitrogen-doped Mo prepared in Example x C / Co / CNT composites include two-dimensional Mo sheets x C substrate and nitrogen-doped carbon nanotubes in-situ grown on the surface of the substrate.
[0094] Figure 3 Figure 1 is the first cycle capacity diagram of the membranes prepared in the first embodiment, the fifth embodiment, the sixth embodiment, and the seventh embodiment at 0.1C. It can be seen that compared with the PP membrane without any improvement, the modified membrane containing only Mo2C MXene (the sixth embodiment), and the Mo2C MXene only doped with nitrogen x C modified diaphragm (seventh embodiment), the first embodiment contains nitrogen-doped Mo x The modified separator of C / Co / carbon nanotube composite material has a significant capacity improvement on lithium-sulfur batteries.
[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nitrogen-doped Mo x C / Co / carbon nanotube composite material, characterized in that The composite material includes nitrogen-doped two-dimensional Mo sheets. x C substrate and a three-dimensional structure consisting of nitrogen-doped carbon nanotubes in situ grown on the surface of the substrate, and the Mo x The C matrix is MoC or a composite of MoC and Mo2C. x Metallic cobalt particles are in-situ grown on the C substrate, and the nitrogen-doped two-dimensional Mo x The nitrogen in the C matrix forms a bond with the matrix in the form of N-Mo; the nitrogen element in the nitrogen-doped carbon nanotube forms a bond in the form of NC; the nitrogen-doped carbon nanotube is in a bent and mutually entangled state, and part of the nitrogen-doped carbon nanotube is from Mo x The C matrix surface extends outward.
2. A nitrogen-doped Mo x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: The steps include: (1) The aqueous dispersion of Mo2C MXene and a cobalt source is stirred to form a non-uniform liquid, and then the non-uniform liquid is rapidly frozen and freeze-dried to obtain a Co-Mo2C MXene precursor for later use; (2) Depositing the heated and gasified carbon source and nitrogen source on the surface of the Co-Mo2C MXene precursor to form nitrogen-doped carbon nanotubes, thereby obtaining the nitrogen-doped Mo x C / Co / carbon nanotube composite material; the carbon source and nitrogen source include at least one of dicyandiamide, melamine and urea.
3. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (1), the Mo2C MXene is a few-layer Mo2C MXene, that is, the number of layers is controlled to be less than 2 to 3.
4. The nitrogen-doped Mo according to claim 3 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: The preparation method of the few-layer Mo2C MXene comprises the steps of: dissolving multi-layer Mo2C MXene in a tetrabutylammonium hydroxide aqueous solution, centrifuging after the reaction is completed, washing the solid product with clean water, and then centrifuging to remove the clear liquid to obtain an aqueous dispersion containing the few-layer Mo2C MXene.
5. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (1), the aqueous dispersion of the Mo2C MXene and the cobalt source is stirred for 12 to 18 hours to obtain the heterogeneous liquid.
6. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (1), the mass ratio of the Mo2C MXene to the cobalt source is 1:1-4.
7. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (1), the cobalt source includes at least one of cobalt acetate, cobalt nitrate and cobalt chloride.
8. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (1), the non-uniform liquid is rapidly frozen with liquid nitrogen and then freeze-dried in vacuum to obtain a powdered Co-Mo2CMXene precursor.
9. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (2), the mass ratio of the carbon source, the nitrogen source and the Co-Mo2C MXene precursor is 1:0.03-0.
125.
10. The nitrogen-doped Mo according to claim 2 x The method for preparing a C / Co / carbon nanotube composite material is characterized in that: In step (2), the carbon source and the nitrogen source are heated and gasified at 800-1000° C. in a protective atmosphere, and kept warm for 1-3 hours under this condition, and the cobalt ions are reduced to cobalt particles to catalyze the growth of nitrogen-doped carbon nanotubes on the surface of the Co-Mo2C MXene precursor.
11. The nitrogen-doped Mo according to claim 1 x C / Co / carbon nanotube composite material or nitrogen-doped Mo obtained by the preparation method according to any one of claims 2 to 10 x Application of C / Co / carbon nanotube composites in the preparation of separators for lithium-sulfur batteries.
12. The use according to claim 11, characterized in that: The preparation of the separator of the lithium-sulfur battery comprises the steps of: (i) The nitrogen-doped Mo x The C / Co / carbon nanotube composite material, the conductive agent and the binder are mixed uniformly, and then a solvent is added and mixed uniformly to obtain a slurry; (ii) The slurry is uniformly coated on the diaphragm, and then vacuum dried to obtain a Mo-doped diaphragm loaded with nitrogen. x Modified interlayer of C / Co / carbon nanotube composites.
13. The use according to claim 12, characterized in that: The mass ratio of the composite material, the conductive agent and the adhesive is 8:1:
1.
14. The use according to claim 12, characterized in that: The conductive agent includes any one of acetylene black and Ketjen black.
15. The use according to claim 12, characterized in that: The binder includes any one of polyvinylidene fluoride and carboxymethyl cellulose.
16. The use according to claim 12, characterized in that: The solvent includes any one of 1-methyl-2-pyrrolidone solution and water.
17. The use according to claim 12, characterized in that: The separator includes any one of a polypropylene microporous membrane, a polyethylene microporous membrane, and Celgard2400.
18. The use according to claim 12, characterized in that: In step (ii), the drying temperature is 50-60° C. and the drying time is 6-24 hours.
Citation Information
Patent Citations
Modified diaphragm for lithium-sulfur battery, preparation method thereof and lithium-sulfur battery with diaphragm
CN107359303A
A method for prepare a nitrogen doped carbon nanotube three-dimensional composite material by in-situ growth of a small lay of titanium carbide
CN109167066A